Contributions of the Programming Conditions for Behavior Development to enable future higher education teachers to program teaching (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Stricto sensu postgraduate courses are characterized by training professionals to be professors and researchers. However, there seems to be an emphasis on the development of research repertoires to the detriment of teaching repertoires, which could support professional practice of future teachers. This study aimed to examine the application of Programming Conditions for the Development of Behaviors principles in a stricto sensu graduate course to enable students to program teaching conditions. The development stages of the discipline are described, from the characterization of learning needs to the construction and application of the teaching program, examining the application of the principles of EAB in this process. The relevance and implications of scientific basis in teaching practice are discussed by using principles and procedures derived from the EAB.
Keywords: Programming Teaching; teacher training; higher education